Inner Voids of Octavinyl Polyhedral Oligomeric Silsesquioxane Acting as Cell Embryos for Polymer Foaming - Jiang, M.; He, L.; Liu, J.; Dong, L.; Xie, H.; Xiong, C. (Asian Journal of Chemistry, 2011)
A new strategy was developed by using octavinyl polyhedral oligomeric silsesquioxane containing inner voids acting as cell embryos to enhance cell structure for polymer foaming through low-cost injection foaming process by using chemical foaming agent. The effect of octavinyl polyhedral oligomeric silsesquioxane on the cell structure was evaluated solely on the basis of cell nucleation. The pre-existing microvoids can lower the activation energy for cell nucleation or even act as cell embryos for polymer foaming. The favourable size and stiff structure of the inner voids are believed to play a crucial role, leading to markedly enhanced cell structure at exceedingly low level, despite the fact that it is not sufficient to obtain fine microcellular structure solely by nucleation effect because of the limited rheological properties.